(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
A product of the marble-making process is marble dust. The cutting process produces a significant amount of powder. Consequently, about 25% of the original marble mass is lost to dust. Directly discharging these waste products into the environment could lead to environmental issues including increased soil alkalinity, negative impacts on plants and people’s health, etc. Concrete can be strengthened by adding marble powder as an addition. It is a stable byproduct of the manufacture of marble that can be used as a cement filler or as fine aggregates in concrete. Concrete that is built using this debris is more affordable and long-lasting, which can assist to address a number of ecological and environmental problems. This study explores the practicality of using marble waste in place of cement to conserve resources and the environment. This study examines the substitution of fine aggregate in concrete with marble dust particles. At content levels of 0, 4, 8, 12, and 16, marble has taken the place of fine aggregate in concrete. Five different series of concrete mixtures were made in order to evaluate the various characteristics of marble dust concrete. Controlled concrete’s workability, compressive strength, water absorption, specific gravity, and other characteristics have all been compared.